Encountering The Syariah Law in Contemporary Era: The Concept of Ijtihād Intiqāiy and Ijtihād Insyāiy - Akil, Andi Amrullah (Al-Mizan (e-Journal), 2025)
This article elaborates on the role of ijtihād in addressing the many problems facing Muslims today. To find solutions, the Muslim community is naturally required to return to the texts of the Qur'an and Sunnah or to examine the results of the ijtihād of previous jurists. However, many of the problems that arise today cannot be solved within classical jurisprudence. Therefore, the door of ijtihād must always be open to realize Islamic law as a law appropriate for every era and place. This study shows that ijtihad is both an obligation that must be carried out and an unavoidable emergency. The author believes that, first, ijtihād intiqāiy is a process of seeking legal certainty regarding a problem. Second, ijtihād intiqāiy is carried out by weighing and comparing opinions from various schools of thought, then examining the basis of their evidence, whether based on the texts of the Qur'an or the Sunnah, or the ijtihad of the companions, and so on. Furthermore, ijtihad on newly emerging problems for which there is no legal determination yet and which are illuminated by shariah arguments is called ijtihād insyāiy. It may even be that ijtihād insyāiy is carried out on problems that existed during the time of the imams of the sect and for which there were legal provisions. However, today's mujtahids can formulate new legal provisions that are more in line with the times, more useful for humans, and closer to realizing the maqāshid al-sharīyah.